Reviews of Tax Planning in Indonesia: The Implementation & Analytical Approach - Nendi Juhandi; Syarifuddin Lakasse (Privietlab, 2022)
The Indonesian government to meet its expenditure needs, requires a definite source of funds every year. Sources of funds for the Indonesian government, among others, are obtained through non-tax revenues and tax revenues. The calculation of income tax in the year for taxpayers is based on the financial statements. Fiscal profit or loss is prepared based on commercial profit or loss which has been adjusted to tax regulations through reconciliation, the reconciliation will result in fiscal improvement. The use of the selection method for calculating income tax article 21 for employees can be one of the applications of taxation methods permitted by the Directorate General of Taxes which can be useful in saving from the tax burden borne by the company. The Company recognizes deferred tax assets only to the extent that it is probable that sufficient taxable profit will be available so that the deductible temporary differences can be utilized (PSAK No. 46, par. 24), or if sufficient taxable profit will be available to compensate the balance. Compensable fiscal loss.